2020
DOI: 10.3390/medicina56020094
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-Based Inspired Approach in Diagnosis of Prostate Cancer

Abstract: Prostate cancer is one of the most encountered cancer diseases in men worldwide and in consequence it requires the improvement of therapeutic strategies. For the clinical diagnosis, the standard approach is represented by solid biopsy. From a surgical point of view, this technique represents an invasive procedure that may imply several postoperative complications. To overcome these impediments, many trends are focusing on developing liquid biopsy assays and on implementing them in clinical practice. Liquid sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 113 publications
(106 reference statements)
0
6
0
1
Order By: Relevance
“…Downregulated expression of miR-139-5p promotes prostate cancer progression by targeting SOX5 [19]. Further, miRNAs also can be invoked as potential prognostic biomarkers in prostate cancer [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Downregulated expression of miR-139-5p promotes prostate cancer progression by targeting SOX5 [19]. Further, miRNAs also can be invoked as potential prognostic biomarkers in prostate cancer [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small non-coding RNAs comprising approximately 22 nucleotides that regulate target gene expression by binding to the 3′ untranslated region (UTR) of target mRNAs ( 5 ). Several studies have reported the dysregulation of miRNAs in various types of human cancers, including breast cancer ( 6 ), lung cancer ( 7 , 8 ), and PC ( 9 , 10 ). miRNAs can act as oncogenes or tumor suppressors depending on their target genes.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their tumor-specific deregulation, miRNAs also possess diagnostic potential for PCa detection [ 10 , 17 , 18 ]. In addition, miRNAs have the advantage of being generally stable in various body fluids and thus, they are deemed to be useful biomarkers [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive investigations using malignant and non-malignant prostate tissue have shown that certain miRNAs are also differentially expressed in PCa [ 11 , 13 , 14 , 15 , 16 ]. Furthermore, selected miRNAs possessed diagnostic potential when analyzed in urine and/or blood samples from PCa patients and control subjects [ 10 , 11 , 17 , 18 ]. Particularly, the collection of urine is inexpensive, simple, and non-invasive, whereupon the number of prostatic cells and thus the amount of PCa-specific miRNAs in the urine specimens can be increased by DRE.…”
Section: Introductionmentioning
confidence: 99%